Great War legacies in Serbian culture - Milojković-Đurić Jelena (Balcanica, 2015)
In the aftermath of the Great War, Ivo Andrić published a number of poems, essays and short stories describing the hard-won victorious outcome as transient to the dire reality of the inordinate loss of human lives and suffering. Yet, personal experiences, although perceived as ephemeral, helped to define the historical discourse capturing man’s resolve to persist in his chosen mission. Over time, Serbian literature and fine arts sustained an unfinished dialogue of the past and the present, merging the individual voices with the collective voices to construct the national narrative. The young writer Miloš Crnjanski observed the sights of destruction and despair that seemed to pale in new literary works pertaining to the war. His novel A Diary about Čarnojević was closely related to his own perilous wartime journey as a conscript in the Austrian army. The vastness of Pannonian plains and Galician woods must have invoked a comparison of sorts with another historic chapter recorded in the collective consciousness of his nation: the Great Migration of Serbs led by Patriarch Arsenije III Čarnojević (Crnojević) in 1690. The very title of the novel contained a powerful reference to the migration, and its illustrious historic leader which has not been discussed or explored before.